Urban poverty and rural poverty in different countries: A systematic literature review - Rahayuningrum, Silvia Tri; Khalil, Amber (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
The complex issues on poverty is widespread globally and affecting countries at various levels of economic development. This study examines urban and rural poverty disparities using measurement, comparison, multidimensional analysis, and identifying contributing factors. Rural poverty shows significant reduction, while urban poverty is more complex. Cross-country comparisons reveal widespread rural poverty, influenced by human resources, nutrition, housing, and reproduction. India, China, and Indonesia have conducted more poverty-related research. Poverty reduction exhibits an inverted U-pattern relationship between Urban-Rural Income Ratio (URI) and rural poverty in several countries, with non-agricultural productivity impacting urban areas. Sustainable public policies and managing urban population growth are essential for poverty alleviation. Urban and rural poverty impact children's cognitive abilities and food consumption. Integrated policies are crucial, necessitating further research and community engagement. Longitudinal research and cross-country comparisons provide insights into effective poverty policies in diverse contexts.